THE RELATIONS BETWEEN URBAN PARKS AND PERSONAL WELL-BEING IN BRISBANE, SOUTH-EAST QUEENSLAND, AUSTRALIA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The positive impacts of urban parks on human health have been analysed in many studies, but nearly none of them provide a suitable method to explain quantitatively the satisfaction and dissatisfaction of park uses 01/ personal health Bayesian Belief Network (BBN) was employed to examine individually well-being spirit in relation to the changes of quality of parks and the joyfulness on access to parks. This study aims to find answers for questions 'why and where are people happy or unhappy with their health in connections to urban parks?' The data for Brisbane area were extracted ji-om the quality of f!fe survey in South- East Queellslalld, Australia. 70% data was usedfor learning model parameters